Textbook Adaptation Techniques in a Technology-Integrated Environment by an Indonesian EFL Teacher - Mustofa, Muhammad Ibnu; Damayanti, Ika Lestari (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2024)
Research on the roles of textbooks in EFL teaching contexts has been widely reported. However, studies on textbook adaptation strategies in a technology-integrated classroom have not received much attention. To fill the gap, the current research sought to explore the types of textbook adaptation strategies employed by an Indonesian EFL teacher in a technology-integrated teaching environment. The challenges encountered and the coping strategies used by the teacher were also investigated. Through a qualitative case study design, an English teacher of an Islamic junior high school in Medan was purposively recruited as the participant. An interview and document analysis were employed to collect the data. The interview data were analyzed using a thematic analysis while the documents were through skimming, reading, and interpretation. The findings revealed that the teacher employed several adaptive strategies, such as omission, addition, and modification on the assignments, the language skills, student activities, and approaches (conventional to the technology-based classroom) through the use of websites, a projector, and digital tools. It was also found that adapting the textbook was challenged by the varied students' levels of proficiency and learning styles, as well as the students' expectations of the teacher. As the coping strategies, the teacher optimized her skills of technology literacy to design creative and engaging learning materials and included tasks that met the levels of students from low and high-achieving groups. The findings of this study imply the crucial roles of all education stakeholders in providing support for teachers to use textbooks effectively